1995
DOI: 10.3109/01485019508987870
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cytokines on Sperm Motility and Ionophore—Stimulated Acrosome Reaction

Abstract: The effects of soluble products from leukocytes (WBC) on sperm motility and calcium ionophorestimulated acrosome reaction (AR) were examined. Supernatants of mononuclear WBC, isolated from peripheral blood and stimulated by the lectins Phyfolacca americana (pokeweed mitogen) or concanavalin A, caused a weak but significant inhibition of progressive sperm motility. The recombinant cytokine interferon-y (IFN-y) in high concentrations inhibited motility of sperm from 5 of 8 donors tested. The recombinant cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…Thus, the percentage of motility was significantly decreased when spermatozoa were incubated with lo6 activated PMN/mL for 5 h. At 5 x lo6 activated PMN/mL there were decreases in three of four motility parameters studied: the percentage of motility, the curvilinear velocity, and the amplitude of lateral head displacement. A less pronounced inhibition of motility was observed by Fedder and Ellermann-Eriksen [37], which might be explained by the longer incubation time (1 8 h) used if the effect is reversible. Vogelpoel and Verhoef [86] found that PMN is activated for up to 4-6 h after stimulation with phorbol myristate acetate (PMA), while PMA-stimulated PMN were no longer active after 18 h.…”
Section: Interleukin-8 (Il-8)mentioning
confidence: 78%
See 4 more Smart Citations
“…Thus, the percentage of motility was significantly decreased when spermatozoa were incubated with lo6 activated PMN/mL for 5 h. At 5 x lo6 activated PMN/mL there were decreases in three of four motility parameters studied: the percentage of motility, the curvilinear velocity, and the amplitude of lateral head displacement. A less pronounced inhibition of motility was observed by Fedder and Ellermann-Eriksen [37], which might be explained by the longer incubation time (1 8 h) used if the effect is reversible. Vogelpoel and Verhoef [86] found that PMN is activated for up to 4-6 h after stimulation with phorbol myristate acetate (PMA), while PMA-stimulated PMN were no longer active after 18 h.…”
Section: Interleukin-8 (Il-8)mentioning
confidence: 78%
“…Eisermann et al [3 11 could detect a significant inhibitory effect on motility at about 100 times lower concentrations. In other studies it was not possible to detect any effect at all of TNF-a on motility (Table 5 ) [37,42,481; nor did TNF-a in combination with low concentrations of interleukin-1 (IL-I) or interferon-y (IFN-y) show any inhibition of motility [42]. The varying results concerning the effect of TNF-a on sperm motility might be due to differences in sensitivity of sperm from different donors (compare IF"-y below) and differences in biological activity of the TNF-a solutions used.…”
Section: Cytokinesmentioning
confidence: 91%
See 3 more Smart Citations